2020
DOI: 10.1021/acsnano.0c02401
|View full text |Cite
|
Sign up to set email alerts
|

Ultraflexible and Mechanically Strong Double-Layered Aramid Nanofiber–Ti3C2Tx MXene/Silver Nanowire Nanocomposite Papers for High-Performance Electromagnetic Interference Shielding

Abstract: High-performance electromagnetic interference (EMI) shielding materials with ultraflexibility, outstanding mechanical properties, and superior EMI shielding performances are highly desirable for modern integrated electronic and telecommunication systems in areas such as aerospace, military, artificial intelligence, and smart and wearable electronics. Herein, ultraflexible and mechanically strong aramid nanofiber−Ti 3 C 2 T x MXene/silver nanowire (ANF-MXene/AgNW) nanocomposite papers with double-layered struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
404
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 680 publications
(415 citation statements)
references
References 65 publications
11
404
0
Order By: Relevance
“…The results suggested there were a uniform temperature distribution between the two electrodes, which showed its superiority with other wearable heaters. [ 40,41 ] Figure 7d exhibited a specific time‐dependent temperatures’ behavior of composite at low operating voltages from 1 to 4 V. It could be observed that the tested sample consistently rose from room temperature (25 °C) to saturation temperature within 10 s, followed by a remaining constant. Longitudinally, the peak temperatures gradually increased from ≈36 to ≈65 °C as the operating voltage changed.…”
Section: Resultsmentioning
confidence: 96%
“…The results suggested there were a uniform temperature distribution between the two electrodes, which showed its superiority with other wearable heaters. [ 40,41 ] Figure 7d exhibited a specific time‐dependent temperatures’ behavior of composite at low operating voltages from 1 to 4 V. It could be observed that the tested sample consistently rose from room temperature (25 °C) to saturation temperature within 10 s, followed by a remaining constant. Longitudinally, the peak temperatures gradually increased from ≈36 to ≈65 °C as the operating voltage changed.…”
Section: Resultsmentioning
confidence: 96%
“…First, although carbon materials and MXene nanosheets can be well dispersed in a solution, during the spraying or filtration process, the MXene nanosheets tend to self-stack when the solvent decreases. Although some reports have employed a layer-bylayer assembly method to avoid aggregation problems [26,[33][34][35], this is a complicated process. Second, the filtration process for 2D materials is time-consuming and unsuitable for large-scale production.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there remains much to learn about these systems using, for example, in situ characterization, precise control, mass production, mechanism exploration, and functional application of noble‐metal composites. On the other hand, the versatile design of noble‐metal composites allows them to be used in other interesting emerging fields, covering electromagnetic interference (EMI) shielding, [ 285–287 ] printing, [ 288–291 ] biotechnology, [ 292–294 ] sensors, [ 295–298 ] and solar energy. [ 299–301 ] Based on the unique features of noble‐metal composites, combined with their finely tuned component and structure design, noble‐metal composites can be produced at low cost and in batches, which further promotes their application in the fields of optics, catalysis, medicine, and electricity.…”
Section: Resultsmentioning
confidence: 99%